Rules Regarding the Use of the REGES-ONLINE Application - Elena STĂNCIULESCU (CECCAR Business Review, 2025)

(untitled)
In this article we want to highlight the categories of employers targeted by REGES-ONLINE, what are the rules regarding data completion, the types of information to be transmitted in the application, what obligations do employers who have contracted the service of completing and transmitting data in the Register have, and what the personal file of employees employed under an individual labour contract contains. Also, REGES-ONLINE users need to know how employees/former employees, as well as employers, access the application and what are the documents required to authorize access.